Digital wedding photography for dummies - Murphy, Amber (--For dummies., 2013)
Murphy provides expert advice on becoming a successful wedding photographer. A hands-on guide to selecting the right equipment, developing the skills and techniques need to create stunning images, and getting your name out to potential clients --